Integrating sleep, sedentary behaviour, and physical activity research in the emerging field of time-use epidemiology: definitions, concepts, statistical methods, theoretical framework, and future directions (Kinesiology, 2017)
Nearly 70 years of sleep, sedentary behaviour, physical activity, and time-use research has led to the recent development of time-use epidemiology. To conceptualise the emerging research field and provide a framework for its further development, this paper defines its position among established branches of science, explains its main concepts and defines associated terms, recommends suitable data analysis methods, proposes a theoretical model for future research, and identifies key research questions. Time-use epidemiology is defined as the study of determinants, incidence, distributions, and effects of health-related time-use patterns in populations, and methods for preventing unhealthy time-use patterns and achieving the optimal distribution of time for population health. As a theoretical model for future studies, this paper proposes The Framework for Viable Integrative Research in Time-Use Epidemiology (VIRTUE framework), acknowledging the compositional nature of time-use data and incorporating research on: 1) methods in time-use epidemiology; 2) outcomes of time-use composition; 3) optimal time-use balance and its prevalence in populations; 4) determinants and correlates of time-use composition; and 5) effectiveness of time-use interventions. It is likely that in total more deaths worldwide can be attributed to unhealthy time use than to smoking or obesity, potentially making it the most relevant modifiable behavioural and lifestyle risk factor of our time. We hope that governments and leading health organisations will recognise the enormous importance of healthy time use, and provide adequate support for future research in time-use epidemiology.